2015
DOI: 10.4028/www.scientific.net/amm.773-774.1163
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ferric Chloride and Chitosan as Coagulant to Remove Turbidity and Color from Landfill Leachate

Abstract: Abstract. Coagulation and flocculation are two of the most common chemical treatment methods used in leachate treatment. Existing coagulants are mainly based on Al and Fe salts. The use of nonchemical based coagulants, especially natural polymers, in leachate treatment has not been thoroughly investigated. Natural coagulants have less harmful effects to human health compared with metal salts. This study aimed to investigate the effectiveness of ferric chloride (FeCl 3 ) and chitosan as coagulant in removing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Figure (4): Effects of pH value on MB and MO removal using FeCl3 aided with lime 3.4 Adsorption isotherm Table (4) summerized the adsorption isotherms with correlation coefficients. The values R 2 of MO and MB for Langmuir isotherm were 0.998 and 0.912 respectively, which is higher than that obtained from Freundlich isotherms[4,6,30]. This indicates that Langmuir isotherm fully describes the nature and the sorption mechanism of MO and MB by chemical coagulation process.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Figure (4): Effects of pH value on MB and MO removal using FeCl3 aided with lime 3.4 Adsorption isotherm Table (4) summerized the adsorption isotherms with correlation coefficients. The values R 2 of MO and MB for Langmuir isotherm were 0.998 and 0.912 respectively, which is higher than that obtained from Freundlich isotherms[4,6,30]. This indicates that Langmuir isotherm fully describes the nature and the sorption mechanism of MO and MB by chemical coagulation process.…”
mentioning
confidence: 68%
“…where Co is the initial dye concentration (mg/L), Ce is the dye concentration at equilibrium (mg/L), V is the volume of the used dye solution (L), and m is the mass of the adsorbent used (mg). The Langmuir model is based on the assumption that the surface is uniform with no interactions between adsorbed molecules and that, it has defined adsorption sites [16,30]. This model considers that adsorption takes place through the formation of an adsorbate monolayer and leads to the equation ( 2),…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…Insufficient dose or overdosing leads to poor flocculation performance of the coagulant. Therefore, the optimal coagulant dose must be identified to reduce dosing costs and obtain optimal removal rates [55]. Due to the filtration The turbidity removal activity of the bio-coagulants may also be affected by changes in the molecular size or rearrangement of the monosaccharides of the polysaccharide chains in alkaline media [46,50].…”
Section: Effect Of Bio-coagulant Dosage On Turbidity Removalmentioning
confidence: 99%
“…Insufficient dose or overdosing leads to poor flocculation performance of the coagulant. Therefore, the optimal coagulant dose must be identified to reduce dosing costs and obtain optimal removal rates [55]. Due to the filtration stage, which retains approximately 70% of the insoluble powder precursors during bio-coagulant preparation, we chose to quantify the coagulant dose in units of (mL/200 mL) rather than (mg/L).…”
Section: Effect Of Bio-coagulant Dosage On Turbidity Removalmentioning
confidence: 99%
“…Nevertheless, chemical coagulants may have adverse effects on the environment. Hence, it is suggested that chitosan could be a better alternative (Verma et al 2012;Ramli and Aziz 2015;Nascimento et al 2016). Nascimento et al (2016) carried out a determination of the optimum dosage and pH values for coagulation-flocculation of biologically treated leachate using chitosan as biocoagulant for the removal of recalcitrant organic matter.…”
Section: Post-treatment Of Sanitary Landfill Leachatementioning
confidence: 99%